2022
DOI: 10.1242/jcs.260529
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of macrophage IFNγ-stimulated gene expression by the transcriptional coregulator CITED1

Abstract: Macrophages serve as a first line of defense against microbial pathogens. Exposure to interferon-γ (IFNγ) increases interferon-stimulated gene (ISG) expression in these cells, resulting in enhanced antimicrobial and proinflammatory activity. Although this response must be sufficiently vigorous to ensure the successful clearance of pathogens, it must also be carefully regulated to prevent tissue damage. This is controlled in part by CBP/p300-interacting transactivator with glutamic acid/aspartic acid-rich carbo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…The differences between CITED1 and 2 go beyond the regulation of their expression and localization and extends to their function with the two transcriptional regulators exerting opposing effects on macrophage pro-inflammatory gene expression. This was shown by Subramani et al using a complementary loss-and gain-of-function approach, where it was found that CITED1 enhances STAT1-and IRF1-regulated gene expression in IFNg-stimulated macrophages, increasing transcript levels of Ccl, Isg, and Ifit family members amongst many others (113). These data suggest that CITED1 is functioning as a transcriptional co-enhancer (Figure 2C), versus the largely coinhibitory effects of CITED2 in the same context.…”
Section: Cited1 a Newly Discovered Regulator Of Macrophage Pro-inflam...mentioning
confidence: 51%
See 3 more Smart Citations
“…The differences between CITED1 and 2 go beyond the regulation of their expression and localization and extends to their function with the two transcriptional regulators exerting opposing effects on macrophage pro-inflammatory gene expression. This was shown by Subramani et al using a complementary loss-and gain-of-function approach, where it was found that CITED1 enhances STAT1-and IRF1-regulated gene expression in IFNg-stimulated macrophages, increasing transcript levels of Ccl, Isg, and Ifit family members amongst many others (113). These data suggest that CITED1 is functioning as a transcriptional co-enhancer (Figure 2C), versus the largely coinhibitory effects of CITED2 in the same context.…”
Section: Cited1 a Newly Discovered Regulator Of Macrophage Pro-inflam...mentioning
confidence: 51%
“…While Cited2 expression is ubiquitous, Cited1 is largely restricted to a small number of tissues (113), and was thought to be absent in macrophages (85). This perception was changed in 2020 when Cited1 transcripts were detected in M1-polarized RAW264.7 murine macrophage-like cells infected with the fungal pathogen, Cryptococcus neoformans (114).…”
Section: Cited1 a Newly Discovered Regulator Of Macrophage Pro-inflam...mentioning
confidence: 99%
See 2 more Smart Citations
“… 62 Studies indicated that prolonged exposure of adipose tissue macrophages to interferon-γ can increase the expression of interferon-stimulated genes such as CITED1, resulting in adipose tissue “browning” and enhanced pro-inflammatory activity. 63 , 64 However, it has not been confirmed whether excess lactate released during adjacent adipose tissue “browning” can promote tumor progression. 65 It is believed that with further research, the relationships of CITED1 with tumor development and progression through beige fat will be elucidated.…”
Section: Association Of Cited1 With Beige Fatmentioning
confidence: 99%